Microchannel plate fabrication using glass capillary arrays with Atomic Layer Deposition films for resistance and gain. Issue 8 (12th August 2016) - Popecki, M. A.; Adams, B.; Craven, C. A.; Cremer, T.; Foley, M. R.; Lyashenko, A.; O'Mahony, A.; Minot, M. J.; Aviles, M.; Bond, J. L.; Stochaj, M. E.; Worstell, W.; et al.
Abstract: Microchannel plates (MCPs) have been used for many years in space flight instrumentation as fast, lightweight electron multipliers. A new MCP fabrication method combines a glass substrate composed of hollow glass capillary arrays with thin film coatings to provide the resistive and secondary electron emissive properties. Using this technique, the gain, resistance, and glass properties may be chosen independently. Large‐area MCPs are available at moderate cost. Secondary emission films of Al2 O3 and MgO provide sustained high gain as charge is extracted from the MCP. Long lifetimes are possible, and a total extracted charge of 7 C/cm 2 has been demonstrated. Background rates are low because the glass substrate has little radioactive potassium 40. Curved MCPs are easily fabricated with this technique to suit instrument symmetries, simplifying secondary electron steering and smoothing azimuthal efficiency. Key Points: MCPs can be made using glass substrates and ALD films The resistance, gain, and substrate are independently selectable with ALD MCPs ALD MCPs are easily made in curved, nonplanar formats